Online Participant Videos: A New Type of Data for Interpretative Social Research? - Schmidt, Robert; Wiesse, Basil (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2019)
In this article, online participant videos (OPVs) are defined as audiovisual participant accounts of social situations and events, and simultaneously as components of social media, online video culture and their technical, media and social logics. We demonstrate that OPV is a multi-layered and meaningful type of data which—depending on the genre—often documents a sociologising of the participants, and which can be used profitably in interpretative video analysis. We present different procedural steps of analysing OPV, based on our experiences from teaching research projects, especially in the context of the sociology of political protest. This shows that the analytical possibilities provided by OPV lie especially in the field of the interpretative sociology of affect.